Jiangjue chixing he hanwei Mao zhuxide "Sanjiehe" de zhengque fangzhen, yiqie quanli gui Shanghaishi geming weiyuanhui
'Firmly uphold and defend Chairman Mao's correct policy of the "Three-in-one combination", all power must return to the Shanghai revolutionary committee'. Printno. T8081.9945.